The Dual Pathways to Customer Recommendation: Service Quality and Perceived Value in the Car Wash Industry - Wisnu Mahendri; Muhammad Sidiq (University of Merdeka Malang, 2025)
This study examines the distinct mechanisms through which service quality and perceived value drive positive word-of-mouth (WOM), focusing on the mediating role of customer satisfaction among 120 customers of Papak Auto Care in Jombang, Indonesia, utilizing Structural Equation Modeling (SEM-PLS). Findings indicate that both service quality and perceived value significantly influence customer satisfaction, with perceived value exerting a more dominant effect (β=0.531) compared to service quality (β=0.409). Crucially, the study identifies two distinct pathways to WOM: service quality does not have a direct significant impact on WOM (P-value=0.396) but is fully mediated by customer satisfaction (β=0.122) , suggesting that satisfaction is a prerequisite for service quality-driven recommendations. Conversely, perceived value demonstrates a strong and direct significant influence on WOM (β=0.489) , indicating that superior value perception can spontaneously trigger customer advocacy. This research contributes by differentiating the impact of process-based evaluations (service quality) and holistic outcome-based evaluations (perceived value) on WOM, offering strategic implications for service providers to focus on service quality to build satisfaction and proactively enhance perceived value for direct WOM stimulation.